2010
DOI: 10.1002/ca.20915
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pelvic anatomy of nerve‐sparing radical hysterectomy

Abstract: Many reports regarding nerve-sparing radical hysterectomy have been published. However, most reports have been based on systematic descriptions via laparotomy or cadaver dissection. The aim of this work was to describe the pelvic anatomy of nerve-sparing radical hysterectomy via laparoscopy, with specific focus on the inferior hypogastric plexus. This study is based on 125 patients with FIGO stage IB cervical cancer who had undergone laparoscopic nerve-sparing radical hysterectomies since 1999. The inferior hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Present data have indicated that NSRH does not extend the risk of surgery approaches and perioperative surveillance. Depending on our data and other scholars' achievements, (Sakuragi et al, 2005;Papp et al, 2006;Park et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Present data have indicated that NSRH does not extend the risk of surgery approaches and perioperative surveillance. Depending on our data and other scholars' achievements, (Sakuragi et al, 2005;Papp et al, 2006;Park et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our operative technique and concept of NSRH have been described in detail elsewhere (5). The study was approved by the Institutional Review Board (approval number: KNUMC 14-1064) and performed with informed consents.…”
Section: Methodsmentioning
confidence: 99%
“…The availability of better optical systems and the advantage of augmented vision have facilitated unprecedented advances in operative methodology [1]. Laparoscopy allows surgeons to visualize small structures in detail, perform meticulous coagulation, and access deeper spaces, thus achieving amazing dissection levels [2,3]. In addition, these advantages are accompanied by the possibility of performing more precise surgical maneuvers, thus minimizing damage to surrounding tissues in areas where access is difficult.…”
mentioning
confidence: 99%
“…Today, the feasibility of exposing the main somatic and autonomic nerves in the pelvis is well documented [2,3]. In addition, from the ability to preserve autonomic innervation of pelvic organs the so-called ''nerve-sparing'' techniques have developed [6][7][8][9], with growing popularity in surgical oncology [8][9][10][11] and deep endometriosis surgery [12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation